Correlation of clinical, biochemical and skeletal responses to 1alpha-hydroxyvitamin D3 in renal bone disease. - Kanis, J; Earnshaw, M; Henderson, R; Heynen, G; Ledingham, J; Naik, R; Oliver, DO; Russell, R; Smith, R; Wilkinson, R; Woods, C (1977)
Thirty-five patients with bone disease and chronic renal failure (twenty-four on maintenance haemodialysis) were treated for 7--39 months with 1alpha-hydroxyvitamin D3, 2--2.5 microgram daily by mouth. Symptoms (bone pain and muscle weakness) and radiographic appearances improved and plasma alkaline phosphatase returned to normal in the majority of patients (87, 76 and 75% respectively). In contrast, histological appearances in bone improved in only 46% twenty-three patients from whom paired biopsies were available, and this change was not greatly different from that seen in a comparable group of untreated patients. Significant correlations were noted in individual patients between the changes in symptoms, X-rays, plasma alkaline phosphatase and immunoreactive parathyroid hormone and these, in turn, were related to histological changes in bone, although these latter changes were often small. It is concluded that 1alpha-hydroxyvitamin D3 is a useful new drug in the treatment of renal bone disease, but that the evaluation of the response depends critically on the method of assessment used.